Carrier Materials Differences on Bioencapsulation Formulation Affect Bacillus sp. Isolates - Yenny Wuryandari; Penta Suryaminarsih; Safira Rizka Lestari (Nusantara Science and Technology Proceedings, 2023)
Biological agent Bacillus sp. Based on the results of previous research, direct use of isolated microorganisms BCZ14, BCZ16, and BCZ20 was able to suppress Fusarium wilt disease. However, Bacillus sp. formulations in suspension form are less effective when applied in the field. This research focuses on analyzing the viability of three isolates of Bacillus sp. against several combinations of bioencapsulation coating materials. The experimental design used was a completely randomized design with a combination of treatment of three isolates and three types of coating materials, namely sodium alginate (B1), carrageenan (B2), and chitosan (B3) each 2%. Each treatment combination was repeated five times. Based on the experiments that have been carried out, the bioencapsulation formulation using 2% chitosan coating material was able to maintain the viability of the three isolates of Bacillus sp. BCZ14, BCZ16, and BCZ20. The population density of the three isolates of Bacillus sp. persisted consistently from the first week to the last week of observation. Therefore, the 2% chitosan coating material can be said to be able to maintain the viability of Bacillus sp. within six weeks.